Rejection of Bankruptcy/PKPU Petitions Against Apartment Developers Following Sema No. 3 Of 2023: An Analysis of Legal Protection, Substantive Justice, and Legal Certainty for Unsecured Creditors - Rusdinah Rusdinah; Evi Kongres (International Journal of Social Service and Research, 2026)
This study aims to analyse the application of the simple evidentiary principle in bankruptcy cases and Suspension of Debt Payment Obligations (PKPU) against apartment developers after the issuance of the Supreme Court Circular Letter Number 3 of 2023, as well as examine legal protection for concurrent creditors due to the rejection of bankruptcy applications or PKPU. The research method used is normative legal research with a legislative, conceptual, and case approach through the analysis of Decision Number 10/Pdt.Sus-PKPU/2022/PN Niaga Smg, Decision Number 320/Pdt.Sus-PKPU/2022/PN Niaga Jkt.Pst, and Supreme Court Decision Number 1349 K/Pdt.Sus-Pailit/2023. The novelty of this research lies in the analysis of the shift in the meaning of the simple evidentiary principle for apartment developers reviewed from the perspective of substantive justice and legal certainty and its implications for the protection of concurrent creditors. The results of the study show that before the enactment of Supreme Court Circular Letter Number 3 of 2023, the application of the simple proof principle focused on the fulfilment of the elements of the existence of more than one creditor and debts that have matured and can be collected as stipulated in Law Number 37 of 2004. However, after the enactment of Supreme Court Circular Letter Number 3 of 2023, the complexity of the legal relationship between developers and apartment buyers has become the main consideration, so that bankruptcy applications or PKPU tend to be considered as not meeting the simple evidentiary requirements.